Yam (Dioscorea spp) Genetic Variability Enhancement Using Its’ True Botanical Seeds - B. Atnafua (Current Topics in Agricultural Sciences Vol. 2, 2021)
Yam (Dioscorea spp) is produced through vegetative propagation using its areal and underground tuber. As many vegetative propagated crops grown in the country, its improvement work is done through collection, characterization and evaluation of germplasms found at farmers field. This study was done to observe yam (Dioscorea spp) flowering and botanical seed germination for its’ genetic improvement and conservation activities. The study was conducted at Gedio Zone, Wonago district, Ethiopia. A total of 60 yam clones of six different species collected from different major growing regions of the country were used in this study. Botanical seeds obtained from open pollinated field showed variability. Among 60 yam germplasms, 21, 12 and 27 genotypes were male, female and none flowering plants respectively. This showed that female plants are small in yam population compared to male yam plants. In this study, 85 percent of botanical seeds were germinated and gave healthy and, vigor yam seedlings. Hence, there is a possibility of increasing yam genetic variability using its’ botanical seeds obtained through open pollination. Indeed, it will be an alternative way for conserving yam and other root and tuber crops germplasms with botanical seeds to minimize their loss and genetic erosion at field gene banks due to biotic and abiotic factors.